2022
DOI: 10.26553/jikm.2022.13.2.168-179
|View full text |Cite
|
Sign up to set email alerts
|

Health-Promoting Lifestyle Assessment Among Nursing Students In East Kalimantan

Abstract: Nurses as a health professional has a significant role in primary health services in nurturing, and also enabling the community to healthy behavior. Nurse students will become role models for healthy lifestyles and as leaders to enable people to live healthy lives, this is inversely proportional to the possibility of their unhealthy lifestyles since the study period. The purposes of study were to assess the level health-promoting lifestyle among student of nursing and identify the differences in such lifestyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 26 publications
(29 reference statements)
1
3
1
Order By: Relevance
“…[34] Results showed that depression was positively correlated with anxiety ( R = 0.734, P < .001). And depression was found to have a negative correlation with health-promoting behavior ( R = 0.201, P = .001), consistent with previous findings, [27] which reported that health-promoting behavior of nursing students had a negative correlation with depression; consequently, there should be careful monitoring of depression and anxiety among nursing students, as well as effective management approaches to reduce these levels. Regular mental health evaluations should be conducted to identify and intervene in nursing students’ health problems, and individual approaches to providing services tailored to each student should be included.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…[34] Results showed that depression was positively correlated with anxiety ( R = 0.734, P < .001). And depression was found to have a negative correlation with health-promoting behavior ( R = 0.201, P = .001), consistent with previous findings, [27] which reported that health-promoting behavior of nursing students had a negative correlation with depression; consequently, there should be careful monitoring of depression and anxiety among nursing students, as well as effective management approaches to reduce these levels. Regular mental health evaluations should be conducted to identify and intervene in nursing students’ health problems, and individual approaches to providing services tailored to each student should be included.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the average health-promoting behaviors of the subjects were 2.43 (0.45). Compared to 2.31, [50] 2.57, [51] and 2.79, [27] which were found when college students were surveyed in a previous study, health-promoting behaviors of the subjects in this study were found to be moderate. Most of the participants in this study were in their early 20s and were generally less interested in lifestyle-related diseases; therefore, an intervention strategy is required to promote health-promoting behaviors during this period.…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations